Is haemoglobin A1c a step forward for diagnosing diabetes?. (10th November 2009) - Kilpatrick, Eric S; Bloomgarden, Zachary T; Zimmet, Paul Z
Abstract : Eric Kilpatrick, Zachary Bloomgarden, and Paul Zimmet question proposals to diagnose diabetes by raised glycated haemoglobin concentration rather than glucose testing